PLEASE HELP ME I CANT DO IT IVE TRIED SO MUCHThe formula C=5/9(F-32) expresses the relationship between Fahrenheit temperature F, and Celsius Temperature C. Use the formula to convert the given Fahrenheit to its equivalent temperature in the Celsius scale.

4 degrees F= Degree C
lydiaisback123 avatar

Answers

Answer 1
Answer:

Answer:

-15.556°C.

Step-by-step explanation:

To convert the given Fahrenheit temperature to its equivalent temperature in the Celsius scale, we can use the formula:

C = (F - 32) / 1.8

Given that the Fahrenheit temperature is 4°F, we can substitute this value into the formula:

C = (4 - 32) / 1.8

Simplifying the equation:

C = (-28) / 1.8

Calculating the value:

C = -15.556°C

Answer 2
Answer:

bellow.

Step-by-step explanation:

To convert 4 degrees Fahrenheit to its equivalent temperature in Celsius, we can use the given formula:

C = (5/9)(F - 32)

Let's substitute the Fahrenheit value of 4 into the formula:

C = (5/9)(4 - 32)

Now, let's simplify the equation step by step:

1. Subtract 32 from 4:

C = (5/9)(-28)

2. Multiply -28 by 5/9:

C = (-140/9)

Therefore, 4 degrees Fahrenheit is equivalent to approximately -15.6 degrees Celsius.


Related Questions

True or false is Every integer a positive number
The sales tax in Bill's state is 6%. Bill bought a Scion having a sales tax of $820. What was the cost of the car? Round to the nearest dollar. A. $13,666 B. $13,668 C. $13,665 D. $13,667
What value of x makes the equation true?(–12.3) • (–6.9) • 9.5 = x • 9.5 • (–12.3)X=
Consider the function f(x) = 3x - 1. What is f(4)?
When y = x^2, which of the following expressions is equivalent to –y ?

The diagram represents a difference of squares.What are the factors of m2 – 6m + 6m – 36?

a. (m – 2)(m + 18)
b. (m – 3)(m + 3)
c. (m – 4)(m + 9)
d. (m – 6)(m + 6)

Answers

Answer:

Option D (m-6)(m+6)

Step-by-step explanation:

we have

m^(2) -6m+6m-36

Simplify

m^(2) -6m+6m-36=m^(2) -36

we know that

In a difference of square

(a^(2)-b^(2))=(a+b)(a-b)

Remember that

36=6^(2)

therefore

(m^(2)-6^(2))=(m+6)(m-6)

The answer is d. 

Explanation:
To start with, classify the first two terms and factor out the common factor. i.e m is a common factor of m2-6m. By factoring it out we get m(m-6).

Follow the same procedure for terms three and four. ie
6 is a common factor of 6m-36. By factoring out, 6(m-6)
Regrouping
m(m-6)+6(m-6)
By factoring out (m-6), we get:
(m-6)(m+6)

Area is 27,405 cm and height is 18 cm what is the volume?

Answers

The volume would be 493,290cm since your are multiplying the area by height.

Given the following functions f(x) and g(x), solve (f + g)(3) and select the correct answer below:f(x) = 2x + 21

g(x) = x − 24

Answers

Answer:

Let f(x) and g(x) be the function then;

(f+g)(x) = f(x)+g(x)

Given the functions:

f(x) = 2x+21

g(x) = x-24

Solve for : (f+g)(3)

(f+g)(3) = f(3)+g(3)           .....[1]

Put x = 3 in f(x) and g(x) we have;

f(3) = 2(3)+21 = 6+21 = 27

and

g(3) = 3-24 = -21

Substitute these values in [1] we have;

(f+g)(3) =27 +(-21) = 27-21 = 6  

Therefore, the value of (f+g)(3)  is 6


(f+g)(x) = 2x+21 +x-24= 3x -3now put x=3 in order to find (f+g)(3)(f+g)(3) = 3(3) -3= 9-3= 6, i hope this helps 

Length of a rectangle is 2.5 cm and it’sarea is 12.5cm2. Ram found that the breadth of the rectangle is 5 cm while Rahim found that the breadth is 10 cm. Who is correct? Justify your answer.

Answers

Step-by-step explanation:

ram is true because when 2.5 is multiplied to .5 centimeters then answered becomes 12.5 centimeters square

If five times a number is subtracted from twelve times a number, the result is seven less than twice the number. Find the number.

Answers

12x - 5x = 2x - 7

7x = 2x - 7

5x = -7

x = - (7)/(5)

How to do recurring decimal and fraction

Answers

Answer:

What do you mean.....???

ex.....0.444444.......

Remove point.... and Write 9 as denominator

that is 4/9

Other Questions